Acinetobacter calcoaceticus is Well Adapted to Withstand Intestinal Stressors and Modulate the Gut Epithelium - Glover, Janiece S.; Browning, Brittney D.; Ticer, Taylor D.; Engevik, Amy C.; Engevik, Melinda A. (Frontiers in Physiology, 2022)
Background: The gastrointestinal tract has been speculated to serve as a reservoir for Acinetobacter, however little is known about the ecological fitness of Acinetobacter strains in the gut. Likewise, not much is known about the ability of Acinetobacter to consume dietary, or host derived nutrients or their capacity to modulate host gene expression. Given the increasing prevalence of Acinetobacter in the clinical setting, we sought to characterize how A. calcoaceticus responds to gut-related stressors and identify potential microbe-host interactions. Materials and Methods: To accomplish these aims, we grew clinical isolates and commercially available strains of A. calcoaceticus in minimal media with different levels of pH, osmolarity, ethanol and hydrogen peroxide. All strains grew modestly at pH 6, 5 and 4; indicating that these strains could tolerate passage through the gastrointestinal tract. To examine the interactions of A. calcoaceticus with the host, inverted murine organoids where the apical membrane is exposed to bacteria, were incubated with live A. calcoaceticus, and gene expression was examined by qPCR. Results: All strains had robust growth in 0.1 and 0.5 M NaCl concentrations which mirror the small intestine, but differences were observed between strains in response to 1 M NaCl. Additionally, all strains tolerated up to 5% ethanol and 0.1% hydrogen peroxide. Biolog phenotypic microarrays revealed that A. calcoaceticus strains could use a range of nutrient sources, including monosaccharides, disaccharides, polymers, glycosides, acids, and amino acids. Interestingly, the commercially available A. calcoaceticus strains and one clinical isolate stimulated the pro-inflammatory cytokines Tnf, Kc, and Mcp-1 while all strains suppressed Muc13 and Muc2. Conclusions: Collectively, these data demonstrate that A. calcoaceticus is well adapted to dealing with environmental stressors of the gastrointestinal system. This data also points to the potential for Acinetobacter to influence the gut epithelium.